Inclusão digital e cidadania via televisão digital no Brasil. - Américo, Marcos [UNESP]; Carvalho, Angela Maria Grossi de [UNESP] (My University, 2015)
The objective of this paper is to discuss issues related to digital inclusion and citizenship in Brazil, through the approach of public policies gestated by the State in an attempt to insert Brazil in the Information Society via Digital Television through two projects: Brazilian Digital TV System (SBTVD) and the Brazilian National Internet Broadband Plan (PNBL), also called “Brazil Connected”. The methodology used was exploratory, with the procedures of bibliographic and documentary research, with the goal of pointing out how actions have been articulating and gestated by the Brazilian government.

O Objetivo deste trabalho é discutir as questões relacionadas à inclusão e cidadania digital no Brasil, por meio da abordagem das políticas públicas gestadas pelo Estado na intenção de se inserir o Brasil na Sociedade da Informação pela via da Televisão Digital. Como metodologia foi utilizada a pesquisa exploratória, com os procedimentos de pesquisa bibliográfica e documental, com o objetivo de apontar como as ações vêm sendo articulas e gestadas pelo Estado.
Digital inclusion and citizenship via digital TV in Brazil
Keywords: Digital inclusion and citizenship via digital TV in Brazil; Televisão digital; Cidadania digital; Inclusão digital; Sistema brasileiro de televisão digital; Plano nacional de banda larga